Political Communication Strategies of Local Parties in the Implementation of Aceh Peace - M. Rizal Falevi Kirani (UMSU, 2023)
The purpose of this research is to analyse how the political communication strategies of local parties towards the implementation of Aceh peace and the impact of political communication strategies of local parties in the implementation of Aceh peace. This research uses the theory of political communication strategies that are ethical, elegant and professionalThis research uses qualitative research methods. The research informants came from local political parties, representatives of Aceh Nanggroe Party, MoU Helsinki peace negotiators and Aceh peace activists who have information about the object of research with a qualitative approach. The results showed that the political communication strategy is through the control of legislative and executive seats by the local party Partai Aceh and Partai Nanggroe Aceh, aims to initiate both policies and regulations (Qanun) and to increase the bargaining value in communication and policy to the central government towards the Aceh government to realise the points of the Helsinki MoU, Secondly, the full control of the legislative and executive seats by the local party (Partai Aceh and Partai Nanggroe Aceh) and reunited in one command of the Free Aceh Movement, the management of the local government runs according to the expectations and ideals of the Helsinki MoU, in addition to giving birth to Qanuns and decisions that have a direct impact on the people of Aceh.